Study of chip scale wireless interconnect systems and their antennas - Sun, Mei (2008)
The chip scale wireless interconnect systems are analyzed in terms of bit error rate performance and studied in terms of their antennas in this thesis. First, a novel inter-chip RF-interconnect system is proposed and analyzed. The intra-chip wireless interconnect system is analyzed at 25 GHz for various digital modulation schemes. In addition, on-chip antennas for intra-chip wireless interconnects are studied, including dipole antennas, 60-GHz inverted-F and quasi-Yagi antennas, as well as monopoles. A novel intra-chip wireless interconnect system using on-chip meander antennas and ultrawide-band (UWB) radios that operate in 22-29 GHz is analyzed. Furthermore, LTCC-based on-package antennas for inter-chip wireless interconnects are studied, including a discrete beveled UWB antenna, a UWB integrated circuit package antenna (ICPA), and 60-GHz ICPAs. A novel interchip wireless interconnect system using on-package beveled antennas and UWB radios that operate in 3.1-10.6 GHz is analyzed.